2022
DOI: 10.1111/jfpp.17118
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable seeds: A new perspective in future food development

Abstract: Traditionally, vegetables are consumed as ingredients of daily household meals. Before cooking, vegetables are washed thoroughly, unpeeled, and deseeded, followed by chopping into desired shapes and sizes. Vegetable peels and seeds are also byproducts of various food industries. If they are not used, they will contribute significantly to global garbage. On the contrary, developing novel functional foods and food ingredients out of unorthodox sources has become a trending issue among researchers. The focus of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 229 publications
0
3
0
Order By: Relevance
“…Required for metabolic functioning [32] Choline Synthesis of phospholipid membrane, cell function [35] Plant-derived antioxidants, mainly polyphenols, for example, flavonoids, lignans, stilbenes, and phenolic acids, possess a comprehensive array of biological traits, antiaging, anticancer, anti-infectious, anti-inflammatory, antiviral, etc. [36,37]. There are also several micronutrients, including vitamins (fat-soluble and water-soluble), minerals, and trace elements that are required for human health.…”
Section: Biotinmentioning
confidence: 99%
“…Required for metabolic functioning [32] Choline Synthesis of phospholipid membrane, cell function [35] Plant-derived antioxidants, mainly polyphenols, for example, flavonoids, lignans, stilbenes, and phenolic acids, possess a comprehensive array of biological traits, antiaging, anticancer, anti-infectious, anti-inflammatory, antiviral, etc. [36,37]. There are also several micronutrients, including vitamins (fat-soluble and water-soluble), minerals, and trace elements that are required for human health.…”
Section: Biotinmentioning
confidence: 99%
“…But all kinds of plant seeds contain rich nutrients, such as polyphenols, flavonoids, and alkaloids. Therefore, more and more attention should be paid to plant seed nutrition and efficacy [5][6][7][8]. Modern medical studies have confirmed that Trichosanthes kirilowii Maxim.…”
Section: Introductionmentioning
confidence: 99%
“…Modern medical studies have confirmed that Trichosanthes kirilowii Maxim. seeds contain unsaturated fatty acids, protein, amino acids, triterpene saponins, and 16 trace elements [5,6]. Therefore, Trichosanthes kirilowii Maxim.…”
Section: Introductionmentioning
confidence: 99%